Influence of Secondary Salinity Wastewater on the Efficiency of Biological Treatment of Sand Filter. (August 2015) - Khengaoui, Khairia; Mahammed, Mahfoud Hadj; Touil, Youcef; Amrane, Abdeltif
Abstract: As preventive of possible environmental nuisances that can cause discharges water in nature, we undertook this study of the influence of salinity wastewater on the treatment efficiency of a biological filter consisting of dune sand. In this work, we designed six identical columns of filtration with sand from the same region of the N'Goussa city (located in the southeast of Algeria). The filters used are fed with wastewater at six different total salinity rates ranging from 0.065% to 0.265% corresponding to the electrical conductivity of 0.85 mS/cm to 3.5 mS/cm. This filtration efficiency was assessed by monitoring changes in the conductivity and the overall pH of the treated water and the chemical oxygen demand (COD). The results obtained showed that the change in the salinity of sewage water has a negative effect on the degradation of organic matter. Indeed, over the salt content is high, over the effectiveness of the biological treatment is reduced, suggesting in this type of case a prior desalination system and tests are under way in our laboratory.